REPRESENTASI KONFLIK INTERNAL DAN RESILIENSI DALAM LIRIK LAGU “USIK” FEBY PUTRI: ANALISIS WACANA KRITIS MODEL VAN DIJK - Iqbal, Muhammad; Mahliatussikah, Hanik; Hilal, Muhammad Rapiq (UNIVERSITAS PGRI YOGYAKARTA, 2025)
The lyrics of the song “Usik” by Feby Putri represent human psychological dynamics through the use of diction and narratives that describe internal conflicts and resilience efforts. This study aims to analyse the representation of inner conflict and self-recovery mechanisms in the lyrics of “Usik” using Van Dijk's critical discourse analysis approach. The research method used is qualitative with content analysis method, which is carried out through three stages of analysis, namely macro-structure analysis to identify the main theme, superstructure analysis to map the narrative flow, and micro-structure analysis that includes semantic, syntactic, and stylistic aspects. The analysis process is strengthened by data triangulation through audience responses obtained from social media, to ensure the validity of the interpretation. The results reveal that the macro structure of the lyrics of “Usik” describes the struggle to find the meaning of life amidst pressure, while the superstructure forms a transformative narrative that moves from the conflict phase to spiritual resolution. In microstructure, linguistic strategies such as the use of darkness metaphors, imperative requests, and rhetorical repetition succeed in strengthening the emotional and spiritual dimensions. The study concludes that the lyrics of “Usik” not only reflect psychological conflict but also offer a narrative of resilience through spiritual affirmation and intimate language, thus demonstrating the relevance of critical discourse analysis in interpreting the complexity of popular music texts. Keywords: internal conflict, resilience, critical discourse analysis, linguistic strategies, song lyrics.